Strategic information systems plan for the College of Computer Studies - DLSU-PSI - Sta. Ana, Virginia Marie A. (Animo Repository, 2002)
This study develops a three-year Strategic Information System Plan for the College of Computer Studies of the De La Salle University-Professional Schools, Inc. To be able to come up with the strategic information systems plan for the College, the proponent followed the Business Systems Planning (BSP) approached developed by IBM. The approach mainly uses the business processes as the basis for information system support. The activities inside an organization can be classified into three: operational, managerial and strategic. Based on the study of the business processes of the College, activities under a business process may fall under any or all of these levels. Considering the existing information systems, the activities on the operational side are the only ones being supported. Most of the routine activities that can be automated are still handled manually. Needs for the management that can be used for control and monitoring of information and performance are still generated by hand.The proposed application portfolio includes transaction-processing systems that automate daily tasks of the College. Output of these systems will then be gathered by another set of information systems that will process and present the information that the users will need. The design of the portfolio is to have one integrated system for the whole College and is segmented based on the processes that each support. The division of each information system is presented in such a way that it covers all the activities of the process across different functions. This shall ensure that all information requirements of all the participants in the process are considered and, if possible, provided by the systems.